A gene‐stacking approach to overcome the trade‐off between drought stress tolerance and growth in Arabidopsis. (12th November 2018) - Kudo, Madoka; Kidokoro, Satoshi; Yoshida, Takuya; Mizoi, Junya; Kojima, Mikiko; Takebayashi, Yumiko; Sakakibara, Hitoshi; Fernie, Alisdair R.; Shinozaki, Kazuo; Yamaguchi‐Shinozaki, Kazuko
Summary: The molecular breeding of drought stress‐tolerant crops is imperative for stable food and biomass production. However, a trade‐off exists between plant growth and drought stress tolerance. Many drought stress‐tolerant plants overexpressing stress‐inducible genes, such as DEHYDRATION‐RESPONSIVE ELEMENT‐BINDING PROTEIN 1A ( DREB1A ), show severe growth retardation. Here, we demonstrate that the growth of DREB1A‐ overexpressing Arabidopsis plants could be improved by co‐expressing growth‐enhancing genes whose expression is repressed under drought stress conditions. We used Arabidopsis GA REQUIRING 5 ( GA5 ), which encodes a rate‐limiting gibberellin biosynthetic enzyme, and PHYTOCHROME ‐ INTERACTING FACTOR 4 ( PIF4 ), which encodes a transcription factor regulating cell growth in response to light and temperature, for growth improvement. We observed an enhanced biomass and floral induction in the GA5 DREB1A and PIF4 DREB1A double overexpressors compared with those in the DREB1A overexpressors. Although the GA5 DREB1A double overexpressors continued to show high levels of drought stress tolerance, the PIF4 DREB1A double overexpressors showed lower levels of stress tolerance than the DREB1A overexpressors due to repressed expression of DREB1A . A multiomics analysis of the GA5 DREB1A double overexpressors showed that the co‐expression of GA5 and DREB1A additively affected primary metabolism, gene expression and plant hormone profiles in the plants. These multidirectional analyses indicate that the inherent trade‐off between growth and drought stress tolerance in plants can be overcome by appropriate gene‐stacking approaches. Our study provides a basis for using genetic modification to improve the growth of drought stress‐tolerant plants for the stable production of food and biomass. Significance Statement: Many drought stress‐tolerant plants overexpressing stress‐inducible genes, such as DREB1A, show severe growth retardation, but the growth of DREB1A‐ overexpressing Arabidopsis plants is improved by co‐expressing growth‐enhancing genes whose expression is repressed under drought stress conditions. We selected GA5, which encodes a rate‐limiting gibberellin biosynthetic enzyme, as a growth‐enhancing gene, and a multiomics analysis of the GA5 DREB1A double overexpressors showed that the trade‐off between growth and stress tolerance can be overcome by appropriate gene‐stacking approaches.